Effectiveness of Soursop Leaf Extract (Annona muricata l.) on IL-6 Levels in Mammary Sprague dawley Female Rats Induced by Staphylococcus aureus (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Staphylococcus aureus is a Gram-positive bacterium that causes inflammation such as mastitis in the breast. Breast mastitis can occur in nursing mothers and requires first aid or initial treatment. Herbal ingredients can be utilized because they are easily obtained and can be prepared by the community themselves. The study aimed to analyze the effectiveness of soursop leaf extract on IL-6 levels in mammae of female rats Sprague dawley induced by S. aureus. The study was divided into four groups consisting of five rats that were induced by S. aureus 2 x 107 CFU/ml. Group I was given 0.5% Na.CMC, Group II gave 45 mg/kgBW cefadroxil antibiotics, group III administered 100 mg / kgBW soursop leaf extract, and group IV administered soursop leaf extract combined with cefadroxil. Each group was given treatment twice a day for 5 days. IL-6 levels were measured on days 3 and 6. The results of this study showed IL-6 levels in group III were 7.50 Â± 1.74 pg/ml on the 3rd day, and 4.51 Â± 1.47 pg/ml on the 6th day. The results showed there were differences in IL-6 levels in group III (p = 0.037). Soursop leaf extract can be used as a therapy for mastitis caused by S. aureus.